De creche à EMEI em Santiago/RS: estudo sobre o trabalho pedagógico - Brenner, Carmen Eloísa Berlote (2018)
This work checked, based in spechees of assistant professors, municipal system education teachers from Santiago/RS who works with children education (EMEI – Escolas Municipais de Educação Infantil), and system education managers, like the pedagogical job produced in these schools has been constituted with these institutional history. From the theoretical and methodological perspective of the Historical and Dialectical Materialism, the data production happened in Santiago/RS – Brazil. The first data was been produced by surveys, which were answered by all the teachers and assistant professors who were working at these schools. After the data tab, two Municipal Education Managers attended a semi-structured interview, one of them had organized the transition of the kindergartens to educational systems, and other person was who had implemented this transition. Other four teachers and four assistants also attended interviews, but they had been chosen by two requirements. The first one was about the year that they entered in the school, between 2011 and 2012 for the group one, this is because these years were when started the work in the “EMEIs”, and the group two is about the teacher who started work in 1900s, decade that happened the transition of the kindergartens to educational systems. The second requirement consisted in select two assistants and two teachers who have believed that “EMEIs” are recognized as Municipal Schools, and others two who have beloved that these institutions are not recognized yet. Upon the review of the speeches produced by the interviews, there was an interlocution group with the participants, moment that was produced new data and were analyzed the existing ones. The data analysis was made dialectically in four categories: pedagogical job, “EMEIs” historicity, public policies and allegiance professional. At the end can be considerate that the institution is not thought to children, the educational policies present dubiety of meaning, the “EMEI” workers live in a allegiance professional crisis, and a lot of them are just fulfilled their job to the detriment of labor, and, as women, their occupation is mistaken with maternal rights. All these factors ending to result in a weak pedagogical job, that does not get to support this institution as a true Children School.